BUDAYA DALAM UPAYA MENCEGAH KEKERASAN PADA ANAK DENGAN MENANAMKAN NILAI-NILAI MULTIKULTURAL - Muyasaroh, Muyasaroh; Ladamay, Man Arfa’ (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Indonesian people have diversity, both from culture, ethnicity, and race. Often we see on the media that violence occurs in children committed by peers with the term bullying. Based on this, it needs to be introduced to children about multicultural values early on. Elementary school-age children already know these differences, so there needs to be an effort to instill multicultural values by the teacher in collaboration with his parents. Oriented to the above problems, the principal of Muhammadiyah Elementary School, Mr. Ahmad Taufik, S.Pd, as a service partner, sees the importance of this service as an effort to prevent delinquency in students caused by student diversity through the planting of multicultural values by teachers and parents. The method used is in the form of seminars and workshops. At the same time, the results of devotion in the way of understanding of teachers and parents for the importance of multicultural values and can implement them in everyday life. At the same time, the workshop for teachers is to create a student track record book to record all cases that occur in students so that students' records can be known validly. Also, the results of this dedication expected to be able to contribute positively to science, especially the values of diversity and unity of the Indonesian nation, which are always intact and to create a productive, intelligent, and avoidance of child delinquency generation.